Transgenic barley ( Hordeum vulgare L.)expressing the wheat aluminium resistance gene ( TaALMT1 ) shows enhanced phosphorus nutrition and grain production when grown on an acid soil - Delhaize, E.; Taylor, P.; Hocking, P.J.; Simpson, R.J.; Ryan, P.R.; Richardson, A.E.
Barley ( Hordeum vulgare L.), genetically modified with the Al 3+ resistance gene of wheat ( TaALMT1 ), was compared with a non-transformed ibling line when grown on an acidic and highly phosphate-fixing ferrosol supplied with a range of phosphorus concentrations. In short-term pot trials (26 days), transgenic barley expressing TaALMT1 (GP-ALMT1)was more efficient than a non-transformed sibling line (GP)at taking up hosphorus on acid soil, but the genotypes did not differ when the soil was limed. Differences in phosphorus uptake efficiency on acid soil could be attributed not only to the differential effects of aluminium toxicity on root growth between the genotypes, but also to differences in phosphorus uptake per unit root length. Although GP-ALMT1 out-performed GP on acid soil, it was still not as efficient at taking up phosphorus as plants grown on limed soil. GP-ALMT1 plants grown in acid soil possessed substantially smaller rhizosheaths than those grown in limed soil, suggesting that root hairs were shorter. This is a probable reason for the lower phosphorus uptake efficiency. When grown to maturity in large pots, GP-ALMT1 lants produced more than twice the grain as GP plants grown on acid soil and 80
Keywords: ACID SOIL; ALUMINIUM RESISTANCE; PHOSPHORUS; RHIZOSHEATH; ROOT GROWTH